Online peer mentoring and remote learning. (15th March 2021) - Goodrich, Andrew
ABSTRACT: The spread of COVID-19 rapidly altered the way music teachers deliver instruction. Now instead of interacting face to face with their students in a classroom setting, instructors often have to teach their students remotely. This sudden transition from in-person to remote learning presents numerous challenges that require a rethinking of established teaching practices. Peer mentoring, for example, is a widely practiced instructional technique that can provide meaningful learning opportunities for students in remote learning environments. Drawing on the new ecology of learning as a theoretical framework, this review of literature details how educational researchers have investigated online peer mentoring, including how teachers facilitate mentoring, student engagement, mentoring beyond the classroom, and obstacles to online access. Significant findings from this research on online peer mentoring are contextualised by music education research on face-to-face peer mentoring and suggest how music teachers can implement and utilise online peer mentoring in their music classrooms.